Ribonuclease activity as a new prospective disease resistance marker in potato - E. A. Trifonova; S. M. Ibragimova; O. A. Volkova; V. K. Shumny; A. V. Kochetov (Вавиловский журнал генетики и селекции)
Disease resistance is an important characteristic for each variety of potato, and the search for pathogen resistance markers is one of the primary tasks of plant breeding. Higher plants possess a wide spectrum of enzymes catalyzing the hydrolysis of nucleic acids; it is believed that protection against pathogens is the most probable function of the enzymes. RNases are actively involved in several immune systems of higher plants, for example, systemic acquired resistance (SAR) and genetic silencing, hence RNase activity in plant leaves, as a relatively easily measured parameter, can serve as a good marker for the selection of pathogen resistant varieties. We have analyzed sixteen varieties of potatoes permitted for use on the territory of the Russian Federation and tested the correlation of the level of varietyspecifc ribonuclease (RNase) activity with such economically valuable traits as maturity and resistance to viruses, late blight and common scab. In general, the level of RNase activity was varietyspecifc, which was confrmed by very small values of average squared error for the majority of tested varieties. We have detected a statistically signifcant positive correlation of RNase activity in potato leaves with increased resistance of varieties to phytopathogenic viruses, a negative correlation with resistance to scab and an absence of a signifcant connection with maturity and resistance to late blight, regardless of the organ affected by the oomycete. Thus, the level of RNase activity in potato leaves can be used as a selective marker for resistance to viruses, while varieties with increased RNase activity should be avoided when selecting resistance to scab.